2015
DOI: 10.1155/2015/374637
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequence Analysis of the Norovirus GII.4 Sydney Variant in South Korea

Abstract: Norovirus is the primary cause of acute gastroenteritis in individuals of all ages. In Australia, a new strain of norovirus (GII.4) was identified in March 2012, and this strain has spread rapidly around the world. In August 2012, this new GII.4 strain was identified in patients in South Korea. Therefore, to examine the characteristics of the epidemic norovirus GII.4 2012 variant in South Korea, we conducted KM272334 full-length genomic analysis. The genome of the gg-12-08-04 strain consisted of 7,558 bp and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…GIHE confirmed that the sample was infected with the HuNoV GII.4 genotype, and the specimen was sent to the Waterborne Virus Bank (WAVA, Seoul, Korea) in 2013; confirmation that this specimen was the HuNoV GII.4 Sydney variant was reported in a previous study [23]. The complete nucleotide sequence of the GII.4 Sydney variant was analyzed by Park et al [24]. The HuNoV GII.4 variant in 500 µL of phosphate-buffered saline (PBS; pH 7.2) was purchased from WAVA, with a genomic titer of 6.50 log copy number/µL.…”
Section: Virus Stock Preparationmentioning
confidence: 69%
“…GIHE confirmed that the sample was infected with the HuNoV GII.4 genotype, and the specimen was sent to the Waterborne Virus Bank (WAVA, Seoul, Korea) in 2013; confirmation that this specimen was the HuNoV GII.4 Sydney variant was reported in a previous study [23]. The complete nucleotide sequence of the GII.4 Sydney variant was analyzed by Park et al [24]. The HuNoV GII.4 variant in 500 µL of phosphate-buffered saline (PBS; pH 7.2) was purchased from WAVA, with a genomic titer of 6.50 log copy number/µL.…”
Section: Virus Stock Preparationmentioning
confidence: 69%
“…If amplification with primers NV107c(s) [30] and NV156(as) [31] failed, alternative reverse primers NV300II [31], G2SKR [32] and G2R1 [32] were used in GGII strains. For analysis of genetic diversity in GII.2 samples, the partial viral RdRp gene and almost the complete VP1 gene was assessed using GII.2 specific primers [33][34][35][36] (Table S1) in RT-PCR and subsequent nucleic acid sequencing.…”
Section: Rna Extraction Detection Sequencing and Typingmentioning
confidence: 99%
“…Norovirus is one of the most common causes of acute gastroenteritis in people of all ages worldwide. Most previous studies of norovirus have focused on epidemic strains such as GII.4 and GII.17 [28][29][30][31]. However, other genotypes can also cause outbreaks [32][33][34].…”
Section: Discussionmentioning
confidence: 99%